1993
DOI: 10.1149/1.2220877
|View full text |Cite
|
Sign up to set email alerts
|

Electrodes for PbZr x Ti1 − x  O 3 Ferroelectric Thin Films

Abstract: Interface‐related degradation problems in PbZrxTi1−xO3 (PZT) thin‐ film nonvolatile memories have led to the search for alternate electrode materials to replace the conventional metal electrodes. In this work, the suitability of ceramic electronic conductors [e.g., ruthenium oxide false(RuO2false) and indium‐tin‐oxide (ITO)] as contact metallization for ferroelectric PbZrxTi1−xO3 thin films has been investigated using techniques such as Rutherford backscattering spectrometry, x‐ray diffraction, and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…RuO 2 is considered a good electrode for PZT [10], and can act as an oxygen "buffer": any oxygen consumed by the underlying metal being supplied by the RuO2, which can partially convert to Ru, leaving the PZT largely unaffected. Since some oxygen will pass through the RuO2, we introduced chromium, which forms a protective, yet semiconducting oxide scale, thus inhibiting oxygen diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…RuO 2 is considered a good electrode for PZT [10], and can act as an oxygen "buffer": any oxygen consumed by the underlying metal being supplied by the RuO2, which can partially convert to Ru, leaving the PZT largely unaffected. Since some oxygen will pass through the RuO2, we introduced chromium, which forms a protective, yet semiconducting oxide scale, thus inhibiting oxygen diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…4, BLCT shows excellent fatigue endurance at 5 V over 10 10 cycles similar to other bismuthlayered ferroelectrics. This is due to the increase of structural stability induced by decrease in oxygen vacancies (27). Substitution of La and Ce by Bi decreased oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…Bismuth layered perovskite ferroelectric films, SrBi 2 Ta 2 O 9 (24) and (Bi,La) 4 Ti 3 O 12 (BLT) (25), have drawn an interest for ferroelectric random-access memory because of the fatigue-free properties over 10 10 read/write cycles, unlike Pb(Zr,Ti)O 3 (PZT) (26,27 with BLT powder showed that 2P r was maximum when the Bi/La was 3.75/0.25 (33)(34)(35).…”
mentioning
confidence: 99%
“…The non-stoichiometric Sr 1-X Bi 2+2X/3 Ta 2 O 9 ceramics prepared from sol-gel method by Jain et al showed the phase transition temperature at 378°C and 455°C and maximum permittivity of 810 and 1230, respectively, for X=0.15 and 0.30 [22]. Recently Sridarane et al, and Kalaiselvi et al, reported higher Curie temperature and enhanced permittivity at the transition temperature for Sr 1+X Bi 2+(2/3)X (V X Ta 1-X ) 2 showed highest dielectric constant of 1040, 1610 measured at 100 kHz at T c s, 510°C and 955°C for x=0.3 and 0.1 respectively. The loss was found to be minimum in the order of 10 −2 for BBN x=0.3 compared to all other compositions within the temperature range investigated (Fig.…”
Section: Dielectric Propertymentioning
confidence: 99%
“…The interest in Bi-based layer-structured ferroelectric oxides (BLSF) has been raised during the last decade since these materials have high polarization fatigue resistance, and is able to withstand 10 12 erase/rewrite operations [1][2][3][4][5]. The crystal structure and chemical composition of these layered perovskites were systematically studied by Aurivillius [3] in the 1950's with a general formula of (Bi 2 O 2 ) 2+ (A m-1 B m O 3m+1 ) 2-, consisting of m-perovskite units sandwiched between bismuth oxide layers called the family of bismuth layered structured ferroelectrics (BLSFs) [6], where A and B are the two types of cations that enter the perovskite unit.…”
Section: Introductionmentioning
confidence: 99%